Does Good Deed Sacrifice Financial Reward: A Study of SRI Index and Fund Performance in the UK - Zhu, Qizhen (2009)
Socially responsible investment has experienced explosive growth during the past decade. It is interesting to know whether being socially responsible sacrifices financial reward. This study aims to examine the economic performance of SRI. In reviewing the literature, it is found that most of the studies conclude a similar performance of SRI to conventional investment. In this study, performance of both SRI index and SRI funds are compared to the market index. Time series regression based on single index model is adopted. Jensen's alpha, Sharpe ratio, Treynor ratio, information ratio and M square measure are used as the tools to evaluate the performance. My research result shows that, (1) SRI index slightly underperform the market, and (2) SRI funds outperform both the SRI index and market index, and such outperformance is more significant during the global financial crisis in 2008.